Defensins as a promising class of tick antimicrobial peptides: a scoping review - Jiahui Wu; Xia Zhou; Qiaoqiao Chen; Zhiqiang Chen; Jinyu Zhang; Lele Yang; Yuxuan Sun; Guohui Wang; Jianfeng Dai; Tingting Feng (BMC, 2022)
Abstract Background Ticks are hematophagous parasites that transmit an extensive range of pathogens to their vertebrate hosts. Ticks can destroy invading microorganisms or alleviate infection via their rudimentary but orchestrated innate immune system. Antimicrobial peptides (AMPs) are important components of tick innate immunity. Among these humoral effector molecules, defensins are well-studied and widely identified in various species of Ixodidae (hard ticks) and Argasidae (soft ticks). This review was aimed at presenting the characterization of tick defensins from structure-based taxonomic status to antimicrobial function. Main text All published papers written in English from 2001 to May 2022 were searched through PubMed and Web of Science databases with the combination of relevant terms on tick defensins. Reports on identification and characterization of tick defensins were included. Of the 329 entries retrieved, 57 articles were finally eligible for our scoping review. Tick defensins mainly belong to the antibacterial ancient invertebrate-type defensins of the cis-defensins superfamily. They are generally small, cationic, and amphipathic, with six cysteine residues forming three intra-molecular disulfide bonds. Tick defensins primarily target membranes of a variety of pathogens, including Gram-positive and Gram-negative bacteria, fungi, viruses, and protozoa. Since tick defensins have a high degree of variability, we summarize their common biological properties and enumerate representative peptides. Along with the various and potent antimicrobial activities, the role of tick defensins in determining vector competence is discussed. Conclusions Due to their broad-spectrum antimicrobial activities, tick defensins are considered novel candidates or targets for controlling infectious diseases. Graphical Abstract